Reliability evaluation of light emitting diode package - Lin, Junan. (2009)
Light emitting diode (LED) offers high efficiency and energy saving alternative to current light solution. It is believed to have a longer lifespan and higher reliability than conventional incandescent and fluorescent lamps. In this project, the High Brightness White LED from Osram went through accelerated life testing. Under the accelerated environmental condition, namely, temperature and humidity cycling, degradation caused by these 2 factors need to be investigated. Prior to that, the preparation for reliability test had to be careful considered. One consideration was the junction temperature which would vary if self heating exited in the LED during operation. The optical result was sensitive to the junction temperature. In order to avoid this phenomenon, a method used to determine an optimized pulse setting has been found in this project. The Total luminous flux was taken to determine the time to degradation (TTD).Others parameter such as the Scotopic to Photopic flux(SP) ratio and the blue to yellow emission intensity ratio was computed as well. With all these data, a failure analysis could be conducted to determine the underlining failure mechanisms